THE EFFECT OF SHORT MESSAGE ON MEDICATION ADHERENCE AND BLOOD GLUCOSA CONCENTRATE (BGC) VALUE AMONG TYPE II DIABETES MELLITUS (DM) PATIENTS - Hasana LIsa Purba; Kintoko Rochadi; Destanul Aulia (Alta Dharma Publisher, 2019)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia. Type 2 DM management is education, diet regulation, drug therapy, physical exercise, and routine check of BGC to prevent complications from improving the quality of life of patients. The study aimed to examine the effect of short messages on medication adherence and control of BGC values ??in type 2 DM patients. This type of research is a quasi-experimental design, pretest, and posttest with a non-equivalent control group that was applied in this study. The research was conducted at Bromo Medan Health Center. Samples were all type 2 diabetes mellitus patients who were controlled to Medan Bromo Puskesmas for 84 people who were divided into two groups, namely the intervention and control groups. The data collection tool uses a questionnaire. The test used was the Wilcoxon test and the Mann Whitney test. The results showed that the short message was significantly (p <0.05), giving a compliant effect on the rules of taking medication and controlling the BGC value compared to patients with type 2 DM who did not send short messages. This study concludes that quick message delivery effectively improves medication adherence and controls BGC values ??to enhance the quality of life of patients with type 2 diabetes. This study recommended family members to remind for controlling blood glucose levels. An SMS reminder activity program also needs to conduct while implementing the plan. Keywords: short message, medication adherence, blood glucose concentrate, type 2 diabetes mellitus